2015
DOI: 10.1016/j.sab.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence imaging of ion distributions in an inductively coupled plasma with laser ablation sample introduction

Abstract: a b s t r a c tHigh-resolution images of the spatial distributions of Sc II, Ca II, and Ba II ion densities in the 10 mm upstream from the sampling cone in a laser ablation-inductively coupled plasma-mass spectrometer (LA-ICP-MS) were obtained using planar laser induced fluorescence. Images were obtained for each analyte as a function of the carrier gas flow rate with laser ablation (LA) sample introduction and compared to images with solution nebulization (SN) over the same range of flow rates. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…A detailed review of the instrumentation used for these experiments was presented in ref. [12]. A brief overview, including modifications, will be provided here.…”
Section: Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed review of the instrumentation used for these experiments was presented in ref. [12]. A brief overview, including modifications, will be provided here.…”
Section: Instrumentationmentioning
confidence: 99%
“…The fluorescence schemes can be found in ref. [12]. The fluorescence was captured on a gated, iCCD (7361-0001, Princeton Instruments, Trenton, NJ).…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our experiments reported in reference [2], in combination with reports from other groups cited above, suggested that changes in measured ion densities that accompanied the addition of helium to the ablation gas were due to changes in the plasma, the evidence was indirect. Caution is needed in drawing conclusions based on interlaboratory comparisons because of inevitable differences in equipment and procedures.…”
Section: Introductionmentioning
confidence: 55%
“…In a recent paper, we investigated the effectson ion distributions in the ICP of adding helium to argon gas upstream from the ablation cell using laser induced fluorescence (LIF) [2]. We were surprised to find that helium added to the carrier gas led to a decrease in the overall ion densities within the ICP.…”
Section: Introductionmentioning
confidence: 99%